(untitled) (Bangladesh Journal of Psychiatry, 2021)
The psychiatric referral rates in Bangladesh are very low, considering the higher rates of psychiatric morbidity in patients who attend various departments of a hospital. The aim of the study was to know the reason and pattern of psychiatric referrals attending in a tertiary care hospital in Bangladesh. This was a descriptive cross-sectional study conducted in a tertiary care hospital, namely Jalalabad Ragib Rabeya Medical College Hospital (JRRMCH). A total of 631 admitted patients were included consecutively who were referred for psychiatric opinion from other departments of the hospital over a period of one year from January 2019 to December 2019. Data were collected through face-to-face interview using the semi structured questionnaire containing socio-demographic profile, referring departments and reasons for referral. The psychiatric disorders were diagnosed according to diagnostic and statistical manual of mental disorders 5 (DSM 5) criteria and recorded after ensuring confidentiality of the patients and then data were analyzed by using descriptive statistical methods. The results showed that, majority of the patients were female comprising 442 (70.05%) and most of the psychiatric referrals (70.21%) were from the department of medicine and the most common reason for referral was medically unexplained somatic complaints (39.14%), followed by anxiety disorder (13.01%) and acute psychosis (6.51%). The most commonly diagnosed psychiatric disorders were conversion disorder (26.94%) followed by somatic symptom disorders (17.27%), generalized anxiety disorders (16.48%) and major depressive disorder (6.66%). So, encouraging multi-disciplinary interaction is needed for the better psychiatric management of patients who usually attend general hospitals. Bang J Psychiatry 2021;35(1): 10-14